Characteristics of Auxiliary Morphotype-Specific Morphological Indicators of Knee Joint Geometry in Osteoarthritis - Kylymniuk, Liubov (The Ukrainian Scientific Medical Youth Journal, 2025)
Knee osteoarthritis represents a significant global medical and social challenge. Objective: To characterize auxiliary morphological indicators of knee joint geometry in osteoarthritis, with consideration of morphotypes identified using a proprietary clustering system. Radiographic data from 100 cases of medial knee degenerative-dystrophic disease were analyzed. The study included 70 patients (26 (37.14 %) men and 44 (62.86 %) women) with a mean age of 63.56±8.10 years. Degenerative changes were assessed on standard weight-bearing anteroposterior radiographs of the knees. The following radiographic parameters were evaluated: MLSR (Medial-Lateral Joint Space Ratio), fICN (Femoral Intercondylar Notch Index), tICN (Tibial Intercondylar Notch Index), TIA (Tibial Intercondylar Angle), FIA (Femoral Intercondylar Angle), and FTA (Femorotibial Angle). According to the clustering system, four morphotype groups were identified: morphotype I in 21 patients (21.00 %), morphotype II – 38 (38.00 %), morphotype III – 29 (29.00 %), and morphotype IV – 12 (12.00 %). Statistical analysis was conducted using Statistica 13, with significance set at p≤0.05. The average MLSR index for morphotype I was 0.19±0.12, for morphotype II – 0.34±0.24, for morphotype III – 0.44±0.32, and for morphotype IV – 0.67±1.06 (p=0.0008). The mean fICN value was 0.10±0.02 in morphotype I, 0.11±0.03 in morphotype II, 0.13±0.04 in morphotype III, and 0.13±0.03 in morphotype IV (p=0.007). The mean tICN was 0.07±0.04 in morphotype I, 0.06±0.02 in morphotype II, 0.07±0.03 in morphotype III, and 0.07±0.02 in morphotype IV (p=0.17). TIA values were 163.90±5.00° for morphotype I, 160.21±4.19° for morphotype II, 161.33±4.33° for morphotype III, and 163.50±2.28° for morphotype IV (p=0.04). FIA values were 201.57±2.27° in morphotype I, 204.37±4.13° in morphotype II, 203.79±5.05° in morphotype III, and 204.75±5.26° in morphotype IV (p=0.03). An increase in varus deformity was associated with more pronounced intra-articular alterations due to medial compartment overload (τ=+0.28, p=0.00004), as well as narrowing of the femoral intercondylar notch and a higher risk of anterior cruciate ligament injury (τ=+0.21, p=0.002). Changes in TIA and FTA observed in morphotypes II, III, and IV were primarily due to varus alignment of the limb axis, while in morphotype I, they were mainly attributed to degradation of the cartilage and subchondral bone of the femoral and tibial condyles. These findings emphasize the importance of considering individual anatomic and morphologic characteristics for a more accurate assessment of risks and prediction of knee osteoarthritis progression.